APLIKASI TEPUNG LIMBAH PENETASAN DALAM RANSUM UNTUK MENINGKATKAN PRODUKTIVITAS ITIK LOKAL DI KELOMPOK TERNAK DESA GAUM, KECAMATAN TASIKMADU, KABUPATEN KARANGANYAR - Indreswari, Rysca Indreswari; Ratriyanto, Adi (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2017)
The ducks hatchery produces a number of waste comprises empty shells from hatched eggs, infertile eggs, dead embryos, and unhatched eggs. The presence of the waste in large amount can cause an environmental pollution. Furthermore, it has a potential but has not received enough attention in terms of utilization as feed ingredient in poultry ration. It contains a substantial amount of nutrients such as protein and calcium, and can be processed into hatchery waste meal that can be applied as an inconventional feed ingredient in ducks ration. The purpose of this activity was to process the ducks hatchery waste into hatchery waste meal to be applied in the ration of local ducks. We colaborated with the Farmers Group of Sabar Sabar 1 and Subur Subur 2 in the Village Gaum, Tasikmadu, Karanganyar. This activity comprises of two stages. The first stage was instructional methods and dialogue through socialization, whereas the second stage was the practical of the hatchery waste meal production and its application in ration. The benefits of this activity is the application of hatchery waste meal can increase ducks productivity, minimize the costs of ration and can reduce the impact of hatchery waste on environmental pollution.Keywords: hatchery waste, local ducks, ration, farmers